An investigation of culturally competent terminology in healthcare policy finds ambiguity and lack of definition - Julian Grant; Yvonne Parry; Pauline Guerin (Elsevier, 2013)
Abstract Objective : This research explored how the concept of cultural competence was represented and expressed through health policies that were intended to improve the quality and efficacy of healthcare provided to families from culturally marginalised communities, particularly women and children with refugee backgrounds. Method : A critical document analysis was conducted of policies that inform healthcare for families from culturally marginalised communities in two local government areas in South Australia. Results : The analysis identified two major themes: lack of, or inconsistent, definitions of 'culture' and 'cultural competency' and related terms; and the paradoxical use of language to determine care. Conclusions : Cultural competence within health services has been identified as an important factor that can improve the health outcomes for families from marginalised communities. However, inconsistency in definitions, understanding and implementation of cultural competence in health practice makes it difficult to implement care using these frameworks. Implications : Clearly defined pathways are necessary from health policy to inform culturally competent service delivery. The capacity for policy directives to effectively circumvent the potential deleterious outcomes of culturally incompetent services is only possible when that policy provides clear definitions and instructions. Consultation and partnership are necessary to develop effective definitions and processes relating to cultural competence.